2014
DOI: 10.1002/hep.27373
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid desaturase 1 gene polymorphisms control human hepatic lipid composition

Abstract: Fatty Acid Desaturase (FADS) genes and their variants have been associated with multiple metabolic phenotypes including liver enzymes and hepatic fat accumulation but the detailed mechanism remains unclear. We aimed to delineate the role of FADSs in modulating lipid composition in human liver. We performed a targeted lipidomic analysis of a variety of phospholipids, sphingolipids and ceramides among 154 human liver tissue samples. The associations between previously Genome-wide Association Studies (GWAS)-ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 44 publications
(91 reference statements)
11
61
0
1
Order By: Relevance
“…Only a minority of genes associated with NAFLD through candidate-gene analysis have been independently validated in large independent studies or through the use of transmission disequilibrium testing. This short list includes mitochondrial superoxide dismutase 2 (SOD2) 77 , phosphatidylethanolamine Nmethyltransferase (PEMT) 78 , fatty acid desaturase 1 79 and kruppel-like factor-6 (KLF6) 80 . All of these genes were associated with progressive NAFLD rather than NAFLD per se.…”
Section: [H2] Geneticsmentioning
confidence: 99%
“…Only a minority of genes associated with NAFLD through candidate-gene analysis have been independently validated in large independent studies or through the use of transmission disequilibrium testing. This short list includes mitochondrial superoxide dismutase 2 (SOD2) 77 , phosphatidylethanolamine Nmethyltransferase (PEMT) 78 , fatty acid desaturase 1 79 and kruppel-like factor-6 (KLF6) 80 . All of these genes were associated with progressive NAFLD rather than NAFLD per se.…”
Section: [H2] Geneticsmentioning
confidence: 99%
“…However, information on how factors, including n-3 PUFA intakes, health status and ethnicity, may influence the penetrance of the FADS genotype, and in turn the effect size, is relatively unknown. Further research, expanding on the recent research by Wang et al (26) , is also required to determine the functional SNP, as well the molecular mechanism(s) responsible for the effect of the FADS genotype on EPA and DHA status. Wang et al examined the association between six FADS SNP and the lipidomic profile and FADS1-3 expression in liver samples (n 154) and reported all six alleles to be associated with FADS1 (but not FADS2 and 3) gene expression and protein levels, suggesting that the causal variant(s) may be located at FADS1 (26) .…”
Section: Impact Of Fatty Acid Desaturase Genotype On Pufa Statusmentioning
confidence: 99%
“…Further research, expanding on the recent research by Wang et al (26) , is also required to determine the functional SNP, as well the molecular mechanism(s) responsible for the effect of the FADS genotype on EPA and DHA status. Wang et al examined the association between six FADS SNP and the lipidomic profile and FADS1-3 expression in liver samples (n 154) and reported all six alleles to be associated with FADS1 (but not FADS2 and 3) gene expression and protein levels, suggesting that the causal variant(s) may be located at FADS1 (26) . In addition, twenty out of forty-two highly linked SNP Impact of FADS genotype on fatty acid status and cardiovascular health in adultswere located in the transcription factor-binding sites of the locus.…”
Section: Impact Of Fatty Acid Desaturase Genotype On Pufa Statusmentioning
confidence: 99%
“…Moreover, data from genome-wide association study and gene expression profiling as well as functional studies indicate that Fads1 is associated with cholesterol level and coronary artery disease [31], insulin resistance [32], and breast cancer [33], while Fads2 is associated with conditional change of skin, reproductive systems, and intestine [34,35], infant intelligence quotient [36], attention-deficit/hyperactivity disorder [37], breast cancer [33], and statin sensitivity [38]. Recently, Fads genes and their variants have been associated with multiple metabolic phenotypes in humans, that is, three Fads SNPs are not only associated with decreased hepatic expression of Fads1, but also associated with increased total hepatic fat content [39]. Additionally, it is found that Fads1 is reduced in human NAFLD [39].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, Fads genes and their variants have been associated with multiple metabolic phenotypes in humans, that is, three Fads SNPs are not only associated with decreased hepatic expression of Fads1, but also associated with increased total hepatic fat content [39]. Additionally, it is found that Fads1 is reduced in human NAFLD [39]. Together, these findings suggest that Fads1 and its polymorphisms modulate hepatic lipid accumulation by altering gene transcription and lipid composition in human livers, and Fads1 may be a therapeutic target to human NAFLD.…”
Section: Introductionmentioning
confidence: 99%